Implementasi Manajemen Mutu Terpadu Sebagai Strategi Persiapan Sertifikasi Lembaga Pendidikan Islam - Akhmed Reza Fachlevi; Siti Julaiha (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2026)
This study aims to analyze the implementation of Total Quality Management (TQM) as a strategy for certification preparation in Islamic educational institutions. The research employed a qualitative approach using a library research method by reviewing relevant national and international journal articles, books, and scholarly documents related to quality management and educational certification. The collected data were analyzed using content analysis techniques to identify the concepts, principles, and implementation strategies of TQM in supporting certification readiness within Islamic educational institutions. The findings indicate that the implementation of TQM plays a strategic role in enhancing institutional readiness for certification through the strengthening of an internal quality assurance system that is structured, systematic, and sustainable. The application of TQM is based on the principles of customer focus, total involvement, continuous improvement, and data-driven decision-making. Implementation strategies include quality system standardization, human resource capacity building, regular internal evaluations and audits, and strengthening quality-oriented leadership. Consistent implementation of TQM not only supports successful certification processes but also fosters a sustainable quality culture that contributes to improving the competitiveness and overall quality of Islamic educational institutions. Therefore, TQM can serve as an effective framework for achieving continuous institutional development and maintaining educational excellence in a rapidly changing environment.